Social construction of victim’s blame, with special emphasis on criminal procedure against accused for the assassination of Zoran Đinđić, the prime minister of Serbia - Nikolić-Ristanović Vesna Ž. (Temida)
In this paper, the problem of victim blaming is analyzed, in general, and particularly, in the criminal procedure and through the media. Also, the attention is paid to the secondary victimization of family members of murder victims in general, and, especially, in criminal procedure, and when there is the tendency of blaming direct victim. In the first part of the paper the overview of existing theoretical knowledge is given. In the second part, the analyses of social construction of victim’s blame in the case of criminal procedure for the assassination of Zoran Đinđić, the prime minister of Serbia, before and during the starting phase of the trial is done. Additionally, the impact that the entire social climate which accompany the trial can have on the victim’s family members as indirect victims is analyzed.